Intersectionality, Lost in Translation? (Re)thinking inter-sections between Anglophone and Francophone intersectionality - Baril, Alexandre (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
Inspired by the intersectional formulation “All the Women Are White, All the Men Are Black,” this paper suggests that “all feminist intersectional analyses are Anglophone and all Francophone feminists are cisgender” to highlight the exclusion of language issues in Anglophone intersectional analyses and of trans issues in their Francophone counterparts.